Duration of untreated psychosis and need for admission in patients who engage with mental health services in the prodromal phase. (August 2015) - Valmaggia, Lucia R.; Byrne, Majella; Day, Fern; Broome, Matthew R.; Johns, Louise; Howes, Oliver; Power, Paddy; Badger, Steven; Fusar-Poli, Paolo; McGuire, Philip K.
Abstract : Background: It is unknown whether prodromal services improve outcomes in those who go on to develop psychosis, and whether these patients are demographically different from the overall first-episode population. Aims: To compare sociodemographic features, duration of untreated psychosis, hospital admission and frequency of compulsory treatment in the first year after the onset of psychosis in patients who present to prodromal services with patients who did not present to services until the first episode of psychosis. Method: We compared two groups of patients with first-episode psychosis: one who made transition after presenting in the prodromal phase and the other who had presented with a first episode. Results: The patients who had presented before the first episode were more likely to be employed and less likely to belong to an ethnic minority group. They had a shorter duration of untreated psychosis, and were less likely to have been admitted to hospital and to have required compulsory treatment. Conclusions: Patients who develop psychosis after being engaged in the prodromal phase have a better short-term clinical outcome than patients who do not present until the first episode. Patients who present during first episodes may be more likely to have sociodemographic features associated with relatively poor outcomes.